Penerapan Metode Piotroski F-Score Untuk Sistem Rekomendasi Saham Berbasiskan Website - Setiyawanto, Setiyawanto; Rastri Prathivi (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
Stock investment is an important aspect in allocating resources in the hope of gaining profits in the future. The Indonesian capital market shows positive growth at the end of 2022, encouraging investors' interest in investing. The problem currently faced by investors is that many investors still have difficulty analyzing the fundamentals of a company because it takes a long time and the complexity of the implementation techniques means that many experience losses when investing. This research aims to develop a stock investment recommendation system by integrating the Piotroski F-Score Method. This method uses nine criteria to assess company performance and provides a score between 0 and 9. Previous research results show that the Piotroski F-Score is effective on stocks with low Book-to-Market (BM) providing a more accurate picture of financial fundamentals. System development uses an Agile Development approach to develop systems because it allows system development faster than other methods and the tools used in system design are UML (Unified Modeling Language). The results of the research are a website-based stock recommendation system to simplify and speed up the time for making investment decisions, and the results of ADRO, ANTM, ESSA, INCO, and ITMG shares achieved the highest score each with a value of 9. The share value that reached the highest value shows that These shares are worth investing in.